Transferring and delaying words in the book of ( Al bahir Al madid fi tafsir Al Quran almajeed ) li Ibn Ajiba (Raparin Journal of Humanities (RJH), 2024)
This research, tagged with (Transferring and delaying words ) in the book fo (Al bahir Al madid fi tafsir Al Quran Almajeed) li Ibn Ajiba,So this study seeks to highlight the importance of transferring and delaying words by Ibn Ajiba and tries to show the grammatical significance of the miraculous Quranic systems that carry hidden connotations and linguistic secrets can only be reached by reflection and contemplation of the Quranic speech and divine expression The style of( transferring and delaying words)occupied the thought of grammarians in the past, starting from Al farahidy and Sibawayhi, then the grammarians followed them examples , especially Sibawayh, where he focused on the significance of attention and care and alert the addressee by changing the sentence and deviating from the original grammatical structure agreed upon by the grammarians in the Arabic sentence.The phenomenon of transferring and delaying words at the beginning is a grammatical phenomenon and then rhetorical, we find that Al-Jurjani paid attention to it in his book(Dalael Aleajaz) clearly interested and then focused on the importance of the significance of the transformation of words from one place to another place, and the beauty of accuracy in meanings, especially in the Holy Qur'an, because the Qur'anic systems and meanings are not realized by everyone except the expert in Arabic, and this is what made Sibawayh and Al-Jurjani and others to indicate the role of meaning in these transformations that occur in the Arabic sentence. We tried in our study to reveal the phenomenon of transferring and delaying words in ( Al bahir Almadid) with a statement of their significance as much as possible, and God bless you.